2023
DOI: 10.1002/anie.202302255
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐siRNA Nanohybrids for Enhanced Chemodynamic Therapy via Ferritin Heavy Chain Downregulation

Abstract: Ferrous iron (Fe 2 + ) has more potent hydroxyl radical ( * OH)-generating ability than other Fenton-type metal ions, making Fe-based nanomaterials attractive for chemodynamic therapy (CDT). However, because Fe 2 + can be converted by ferritin heavy chain (FHC) to nontoxic ferric form and then sequestered in ferritin, therapeutic outcomes of Fe-mediated CDT agents are still far from satisfactory. Here we report the synthesis of siRNA-embedded Fe 0 nanoparticles (Fe 0 -siRNA NPs) for self-reinforcing CDT via FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…3 c). This partial lysosomal escape can be attributed to the release of Fe 2+ from MSPION3 under acidic condition, which leads to the conversion of intracellular H 2 O 2 into •OH through Fe 2+ catalysis, resulting in membrane damage [ 30 ]. The results of cellular uptake and lysosome escape demonstrate that our MSPION as a generic DDS can deliver SFN and BQR into tumor cells for anti-cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…3 c). This partial lysosomal escape can be attributed to the release of Fe 2+ from MSPION3 under acidic condition, which leads to the conversion of intracellular H 2 O 2 into •OH through Fe 2+ catalysis, resulting in membrane damage [ 30 ]. The results of cellular uptake and lysosome escape demonstrate that our MSPION as a generic DDS can deliver SFN and BQR into tumor cells for anti-cancer therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang et al developed ferritin heavy chain (FHC)-silencing siRNA-embedded iron (Fe 0 -siRNA) nanoparticles. 87 Upon internalization by tumour cells, the Fe 0 -siRNA nanoparticles degraded and released Fe 2+ and FHC-silencing siRNA within the acidic endo/lysosomes while consuming O 2 . On the one hand, the released FHC-silencing siRNA could escape the endo/lysosomes, as a result of CDT-induced cellular membrane disruption, and downregulate FHC to suppress the transformation of Fe 2+ to Fe 3+ , an ionic form that is known to be less CDT effective.…”
Section: Strategies To Improve Cdt Efficiencymentioning
confidence: 99%
“…5,6 Especially, mounting evidence demonstrated that ferrous ions-mediated CDT had great potential in tumor therapy due to high efficiency and low side effects. 7 However, the limited supply of hydrogen peroxide in tumor microenvironment severely impaired the curative effect of CDT. 8 Therefore, the development of hydrogen-peroxideindependent CDT is an urgent clinical need.…”
Section: Introductionmentioning
confidence: 99%
“…Chemodynamic therapy (CDT) is an emerging therapeutic strategy that produces excess free redicals via Fenton or Fenton-like reaction, resulting in irreversible oxidative damage to biological macromolecules. Since it was first proposed in 2016, CDT is considered as a “Trojan Horse” therapeutic regimen that utilizes transition metal nanomedicine (such iron, copper, manganese, cobat) to react with endogenous hydrogen peroxide, finally producing the highly active free radicals which can be applied in the proliferative diseases treatment and antimicrobial infections. , Especially, mounting evidence demonstrated that ferrous ions-mediated CDT had great potential in tumor therapy due to high efficiency and low side effects . However, the limited supply of hydrogen peroxide in tumor microenvironment severely impaired the curative effect of CDT .…”
Section: Introductionmentioning
confidence: 99%